Association between sarcopenia and erectile dysfunction in older males. (March 2022) - Surmeli, Deniz Mut; Karpuzcu, Hulusi Can; Atmis, Volkan; Cosarderelioglu, Caglar; Yalcin, Ahmet; Varli, Murat; Aras, Sevgi
Highlights: The incidence of sarcopenia and erectile dysfunction increases with advancing age. Presence of sarcopenia in older men is associated with increased moderate to severe erectile dysfunction. When the sarcopenia components are evaluated, decreased muscle strength and muscle mass are associated with increased likelihood of moderate to severe erectile dysfunction in older men. In clinical practice, it should be kept in mind that older men with sarcopenia or low muscle strength may have concomitant erectile dysfunction. Abstract: Introduction: In advanced age, both sarcopenia and erectile dysfunction (ED) occur with similar underlying causes through different mechanisms. In our study we investigated the association between sarcopenia and ED in older men. Methods: A total of 193 male patients aged 60 years and older were included in the study. The presence of sarcopenia was investigated in accordance with EWGSOP2 diagnostic criteria. For evaluation of ED, we used the 5-question International Index of Erectile Dysfunction questionnaire with categories of no ED, mild-moderate ED, and moderate-severe ED. Total testosterone levels were measured. Results: The median age of the patients was 71.9 (range 60–93 years). The prevalence of sarcopenia was 24.9%, and moderate-severe ED was 49.2%. Moderate-severe ED was more common in patients with sarcopenia than those without (70.8% vs 42.1%, p < 0.001). After adjustment for age and Charlson Comorbidity Index, the presence of sarcopenia was significantly associated with moderate-severe ED with odds ratio (OR) of 2.71 (95% Confidence Interval [CI] 1.29–5.73, p = 0.009). The components of sarcopenia were assessed separately in multivariate analysis. Muscle strength and muscle mass were significantly associated with moderate-severe ED with OR of 0.93 (95%CI 0.89–0.98) and 0.68 (95%CI 0.54–0.86), respectively, whereas gait speed was not associated with moderate-severe ED. Conclusion: The presence of sarcopenia in older men is associated with an increased risk of moderate-severe ED. In addition, decreased muscle strength and decreased muscle mass are associated with an increased risk of moderate-severe ED. Prospective studies are needed to reveal the causality between sarcopenia and ED.